Stem/Proliferative and Differentiated Cells within Primary Murine Colonic Epithelium Display Distinct Intracellular Free Ca2+ Signal Codes. Issue 22 (12th September 2021) - Mestril, Sebastian; Kim, Raehyun; Hinman, Samuel S.; Gomez, Shawn M.; Allbritton, Nancy L.
Abstract: The second messenger, intracellular free calcium (Ca 2+ ), acts to transduce mitogenic and differentiation signals incoming to the colonic epithelium. A self‐renewing monolayer of primary murine colonic epithelial cells is formed over a soft, transparent hydrogel matrix for the scalable analysis of intracellular Ca 2+ transients. Cultures that are enriched for stem/proliferative cells exhibit repetitive, high frequency (≈25 peaks h −1 ), and short pulse width (≈25 s) Ca 2+ transients. Upon cell differentiation the transient frequency declines by 50% and pulse width widens by 200%. Metabolites and growth factors that are known to modulate stem cell proliferation and differentiation through Wnt and Notch signaling pathways, including CHIR‐99021, N‐[(3, 5‐Difluorophenyl)acetyl]‐L‐alanyl‐2‐phenylglycine‐1, 1‐dimethylethyl ester (DAPT), bone morphogenetic proteins (BMPs), and butyrate, also modulate Ca 2+ oscillation patterns in a consistent manner. Increasing the stiffness of the supportive matrix from 200 Pa to 3 GPa shifts Ca 2+ transient patterns toward those resembling differentiated cells. The ability to monitor Ca 2+ oscillations with the spatial and temporal resolution offered by this platform, combined with its amenability to high‐content screens, provides a powerful tool for investigating real‐time communication within a wide range of primary tissues in addition to the colonic epithelium. Abstract : An automated imaging pipeline platform assesses the intracellular calcium transient patterns of self‐renewing primary colonic epithelial cells. Proliferative and differentiated cells exhibit distinct calcium transient patterns with the proliferative cells exhibiting short‐lived, high‐frequency calcium oscillations, while differentiated cells demonstrate wider and low‐frequency peaks.